PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empirik Pada Perusahaan Perbankan di BEI tahun 2014 – 2016) - Novi Syiti Masitoh; Nurul Hidayah (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2018)
ABSTRACT This study aims to determine the effect of Good Corporate Governance on Banking Performance in BEI period 2014 - 2016. This study analyzes the effect of Public Ownership, Managerial Ownership, Board of Directors Size, Proportion of Independent Board of Directors and Proportion of Independent Commissioners on ROE (Return on Equity ) by multiple analysis methods. The results showed that the size of the Board of Directors has a significant positive effect on ROE and the Proportion of Independent Board of Directors has a significant negative effect on ROE. While other variables of Public Ownership, Managerial Ownership, and Proportion of Independent Commissioner have no effect on company ROE. Keywords:       Good Corporate Governance, Public Ownership, Managerial Ownership, Board of Directors Size, Proportion of Independent Board of Directors and Proportion of Independent Commissioners, and ROE.